2018
DOI: 10.1038/s41388-017-0050-x
|View full text |Cite
|
Sign up to set email alerts
|

The management of retinoblastoma

Abstract: Retinoblastoma (Rb) is the most common primary intraocular malignancy of childhood, but an uncommon paediatric cancer, with a constant incidence worldwide of 1:15,000-1:20,000 live births. Despite its rarity, Rb has served as a cornerstone in the field of oncology in many of the aspects that comprise cancer management, including classification schemes, treatment modalities, genetic testing and screening. Until just over half a century ago, the major treatment for Rb was eye removal, and prognosis was poor with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
147
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(160 citation statements)
references
References 50 publications
1
147
0
2
Order By: Relevance
“…1,2 Despite great progresses in ocularsalvage treatment in the past decades, enucleation remains the only option to save the lives for children who present with advanced disease. 3 High-risk histopathologic features, representing extensive invasion of tumor cells, facilitate in predicting metastasis and mortality. For children with high-risk findings, postoperative adjuvant systemic chemotherapy is frequently administered to reduce the risk of metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Despite great progresses in ocularsalvage treatment in the past decades, enucleation remains the only option to save the lives for children who present with advanced disease. 3 High-risk histopathologic features, representing extensive invasion of tumor cells, facilitate in predicting metastasis and mortality. For children with high-risk findings, postoperative adjuvant systemic chemotherapy is frequently administered to reduce the risk of metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…[18] In developing countries, the survival rate of RB patients is still below 70% . [19] It is urgent to investigate new and effective molecular targets for the treatment of RB. [20,21] In this study, we confirmed that lncRNA-UCA1 could facilitate cell proliferation and inhibit apoptosis through activating PI3K/Akt pathway in RB.…”
Section: Discussionmentioning
confidence: 99%
“…18 In developing countries, the survival rate of RB patients is still below 70%. 19 It is urgent to investigate new and effective molecular targets for the treatment of RB. In this study, 16 ovarian cancer 22 and lung cancer.…”
Section: Rbmentioning
confidence: 99%